Evaluation of 3M Molecular Detection Assay (MDA) 2–Listeria for the Detection of Listeria Species in Select Foods and Environmental Surfaces: Collaborative Study, First Action 2016.07. (22nd November 2019) - Bird, Patrick; Flannery, Jonathan; Crowley, Erin; Agin, James; Goins, David; Monteroso, Lisa; ,
Abstract: 3M Molecular Detection Assay (MDA) 2– Listeria uses loop-mediated isothermal amplification and bioluminescence detection to rapidly detect Listeria species in a broad range of food types and environmental surfaces. Using an unpaired study design, MDA 2– Listeria was compared with the U.S. Department of Agriculture, Food Safety and Inspection Service's Microbiology Laboratory Guidebook Chapter 8.09 "Isolation and identification of Listeria monocytogenes from red meat, poultry and egg products, and environmental samples" reference method for the detection of Listeria in deli turkey and raw chicken breast fillet. Technicians from 13 laboratories located within the continental United States and Canada participated in the collaborative study. Each matrix was evaluated at three levels of contamination: uninoculated control (0 CFU/test portion), low inoculum (0.2–2 CFU/test portion), and high inoculum (2–5 CFU/test portion). Statistical analysis was conducted according to the probability of detection (POD) statistical model. Results obtained for the low-inoculum-level test portions produced a difference between two laboratory POD values (dLPOD) with 95% confidence intervals of 0.04 (–0.08, 0.17) for deli turkey, indicating the difference between the methods was not statistically significant at the P = 0.05. For raw chicken breast fillet, a dLPOD value with 95% confidence interval of 0.16 (0.04, 0.28) indicated a statistically significant difference between the two methods, with an observed higher proportion of positive results by the candidate method than the reference method.